2, 5-hexanedione-induced deregulation of axon-related microRNA expression in rat nerve tissues. (1st March 2020) - Piao, Fengyuan; Chen, Yang; Yu, Li; Shi, Xiaoxia; Liu, Xiaofang; Jiang, Liping; Yang, Guang; Wang, Ningning; Gao, Bihu; Zhang, Cong
Highlights: 2, 5-hexanedione exposure induced neuropathy in treated animals. The axon-miRNAs related to 2, 5-hexanedione induced neuropathy. Axon-related miRNAs mediate 2, 5-hexanedione toxicity by regulating many pathways. Abstract: Exposure to organic solvent in industry, including n-hexane is correlated with central-peripheral axonopathy, which is mediated by its active metabolite, 2, 5-hexanedione (HD). However, the underlying mechanism is still largely unknown. Recently identified microRNAs (miRNAs) may play important roles in toxicant exposure and in the process of toxicant-induced neuropathys. To examine the role of miRNAs in HD-induced toxicity, neuropathic animal model was successfully built. miRNA microarray analysis revealed 105 differentially expressed miRNAs after HD exposure. Bioinformatics analysis showed that "Axon" and "Neurotrophin Signaling Pathway" was the top significant GO term and pathway, respectively. 7 miRNAs both related to "Axon" and "Neurotrophin Signaling Pathway" were screened out and further confirmed by Real-Time PCR. Correspondingly, the deregulation expression levels of proteins of four target genes (GSK3β, Map3k1, BDNF and MAP1B) were further confirmed via western blot, verifying the results of gene target analysis. Taken together, our results showed that the axon-related miRNAs to be associated with MAP1B or neurotrophin signal pathways changed in nerve tissues following HD exposure. These miRNAs may play important roles in HD-induced neurotoxicity.